A Rare Case of Intraductal Papilloma Arising from Minor Salivary Gland in the Floor of the Mouth. (25th August 2020) - Assao, Agnes; de Freitas Filho, Silas Antonio Juvencio; Simonetti Júnior, Luiz Antônio; Oliveira, Denise Tostes
Abstract : A 77-year-old woman with a rare oral intraductal papilloma arising from the minor salivary gland located on the floor of the mouth and causing the mucus retention is reported. Microscopically, the lesion was characterized by unicystic cavity exhibiting the lumen partially filled by papillary projections of the ductal epithelium with varying degree of oncocytic metaplasia. Based on the histopathological analysis, the differential diagnosis of oral intraductal papillomas and other ductal neoplasms of salivary origin are discussed.